Toward an Islamic Smart Governance Framework: Comparative Evidence from Türkiye, Malaysia, and Indonesia - Iskandar, Eddy; Samsurijan, Mohamad Shaharudin; Pratama, Prawira Yudha (Universitas Muhammadiyah Yogyakarta, 2026)
The growing adoption of digital government has encouraged Muslim-majority countries to integrate technological innovation with religious and socio-cultural values in public governance. However, existing studies largely focus on technological readiness and administrative reforms, while limited attention has been paid to how Islamic governance principles shape smart governance implementation. This study examined the interplay between digital policy, institutional capacity, and Islamic values in the development of smart governance in Türkiye, Malaysia, and Indonesia. Employing a comparative qualitative design, the research utilized a Most Similar System approach to analyze three countries that share Islamic socio-political characteristics but exhibit different trajectories of digital transformation. Data were collected through semi-structured interviews with government officials, academics, and civil society representatives, complemented by policy documents, government reports, and scholarly literature. The findings reveal that smart governance performance is influenced not only by technological infrastructure but also by the institutionalization of Islamic governance values. Türkiye demonstrates a technology-driven model characterized by advanced digital integration and administrative efficiency. Malaysia exhibits a value-oriented model in which the principles of amanah (accountability), ‘adl (justice), and shura (consultative governance) are explicitly embedded in public policy. Indonesia represents a regulatory-driven model supported by the Electronic-Based Government System (SPBE), although implementation disparities persist across local governments. The study proposes an Islamic Smart Governance Framework that highlights the synergistic relationship between institutional capacity, digital innovation, and Islamic ethical values in enhancing transparency, participation, and public trust. These findings contribute to the literature on digital governance by offering a contextualized perspective on smart governance in Muslim-majority societies.